Hydrological structure of the waters in the Drake Passage based on the survey of December, 2018 - V. Komorin; Y. Dykhanov; V. Bolshakov; Y. Popov; E. Melnik; L. Savinykh-Paltseva (Ukrainian Antarctic Journal, 2020)
The results of the analysis of hydrological observations made on the Ukrainian fish-krill trawler "More Sodruzhestva" in the south-eastern part of the Drake Passage in December, 2018 are presented in article. The aim of the investigation is to study the thermohaline structure of the 200 m surface water layer in the research area and comparison of the actual state of the water masses in the summer of 2018 with those identified during previous studies. The expedition was carried out at the hydrological polygon from eight stations. Measurements were conducted by the sensing complex СTD SBE 37SM. Traditional methods for graphic and statistical analysis have been used to process the obtained data. Water structures were allocated based on the analysis of the T,S and O2,σ-diagrams. In addition, satellite data of the Marine Environment Monitoring Service from the Copernicus website as well as information from one of the drifting buoys of the Project ARGO which took place through the research area during this time were involved in the analysis. The results are the spatial hydrological structure of the upper 200 m water layer in the research area. The main water masses formed this structure, as well as the actual position of the Polar Front in the north and the Scotia Sea Front in the south. Characteristics of the spatial variability of the cold intermediate layer are highlighted. The largest volume of water was occupied by the Southern Front of the Southern branch of the ACС that moves the relatively desalinated surface waters of the Bellingshausen Sea in this layer; there is a significant role of the influence of dynamic factor on the distribution of hydrological characteristics. It is noted that the on-site surveillance data are well consistent with the in for mation obtained from Copernicus and the Project ARGO.